Corrosion Behavior and Passive Film Composition of Alloy 825 in High Temperature and High H2S-CO2 Containing Environment - Feng, Zhe; Fan, Xuehua; Wang, Zhu; Yu, Yong; Chen, Lijuan; Du, Yanxia; Dong, Lei (Frontiers in Materials, 2021)
The effect of high temperature on corrosion behavior and passive film composition of Ni-based alloy 825 in H2S-containing environment was investigated by CLM, SEM, EDS and XPS. The results indicated that Ni-based alloy 825 exhibited good general corrosion resistance. The pitting corrosion was more likely to occur at high temperature due to the depletion of Cr in the passive film. NiS appeared at high temperature which is detrimental to protectiveness of passive film.